Evaluation of immune checkpoint inhibitor efficacy for solid tumors with CD274 (PD-L1 gene) amplification identified by comprehensive genomic profiling: retrospective study based on a nationwide database - Hidetoshi Hayashi; Yasutaka Chiba; Kazuhiko Nakagawa; Tomohiro Nakayama; Kimio Yonesaka; Takayuki Takahama; Hisato Kawakami; Naoki Shiraishi (Journal for ImmunoTherapy of Cancer)
Background Amplification of the programmed cell death-ligand 1 gene (CD274) is highly prevalent and associated with a high response rate to immune checkpoint inhibitors (ICIs) in lymphomas, and is also a potential biomarker for ICI treatment of solid tumors. However, the efficacy of ICIs for solid tumors with CD274 amplification identified by comprehensive genomic profiling (CGP) has been unclear. We here examined ICI efficacy for solid tumors with CD274 amplification identified by CGP in a national database.Methods We retrospectively analyzed data from the Center for Cancer Genomics and Advanced Therapeutics database containing 60,155 CGP test results for individuals with solid tumors. Only clinical data from patients treated with ICIs alone (not those undergoing concomitant therapy with molecularly targeted or cytotoxic chemotherapeutic agents) were evaluated. We matched 48 patients in the CD274 amplification-positive group with 170 patients in the CD274 amplification-negative group in a 1:4 ratio based on tumor type, histology, treatment, and age. Overall survival (OS), time to next treatment (TTNT), and response rate were evaluated as treatment outcomes in the two groups.Results OS was similar in the CD274-amplified and matched CD274-non-amplified groups (median of 22.1 vs 26.3 months, respectively; HR of 0.92 with a 95% CI of 0.55 to 1.54; p=0.075). TTNT tended to be longer in the CD274-amplified group than in the matched CD274-non-amplified group (median of 16.5 vs 14.0 months; HR of 0.63 with a 95% CI of 0.37 to 1.08; p=0.091). The objective response rate was 33.3% and 18.4% (difference of 14.9%, with a 95% CI of –0.2% to 31.6%), and the disease control rate was 63.9% and 41.1% (difference of 22.8%, with a 95% CI of 5.1% to 40.4%), in the CD274-amplified and matched CD274-non-amplified groups, respectively.Conclusions The number of patients with solid tumors positive for CD274 amplification in this analysis is the largest to date, and our results suggest that such gene amplification may be associated with the outcome of ICI treatment in such individuals. CD274 amplification identified by CGP may therefore be a predictor of ICI efficacy for solid tumors.Trial registration number UMIN000029779.